Intra-Arterial Chemotherapy: New Hope for Adult Retinoblastoma Treatment—A Case Report and Brief Review - Hamid Riazi-Esfahani; Babak Masoomian; Fariba Ghassemi (Case Reports in Ophthalmological Medicine, 2021)
Background. Adult retinoblastoma (RB) is a rare intraocular tumor, leading to delayed diagnosis and, eventually, enucleation of the involved eyes. Therefore, this diagnosis should be considered if attributable signs and symptoms occurred. Here, the authors report a case of an adult group D RB, treated successfully with intra-arterial chemotherapy (IAC) as primary treatment followed by cryotherapy. The authors briefly review the literature on the prognosis and management of adult RB. Case Presentation. A 22-year-old man has noticed floaters in his right eye for 2 months. Right eye examination revealed diffuse white spherical calcified vitreous seeds in all quadrants and a large white endophytic mass in the superonasal quadrant with engorged feeding vessels. Based on clinical data, the group D RB tumor was classified and the IAC was started with 2 medications, melphalan (5 mg) and topotecan (1 mg), for 3 cycles. Trans-scleral triple freeze-thaw cryotherapy was used as an adjunctive treatment at the latest hospital visit. Thirteen months after the last treatment, the RB tumor showed type 4 regression (flat chorioretinal scar) and no evidence of recurrence was identified. Conclusion. It seems that IAC, as the first line of treatment, either alone or in conjunction with adjuvant therapies may allow us to salvage the globe of adult patients involved with RB.